Competencies and Training Needs in Epidemiology: 2023 Public Health Workforce in Health Region 9 - Chongkratok, Phimruethai; Yueayai, Khanuengnij; Sukkasem, Inchat; Sanmai, Sattawat (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2024)
The Field Epidemiology Training Center (FETC) plays a crucial role in developing the workforce in the field of epidemiology. The Epidemiology Division of the Department of Disease Control has established standards and guidelines for developing the capacity of the Surveillance Rapid Response Team (SRRT). However, there may still be a lack of understanding regarding individual competencies to reflect the efficiency of their work and the need for epidemiology knowledge development. Therefore, the study was conducted to assess the competencies and development needs in the field of epidemiology. A cross-sectional study design was used, focusing on public health personnel working in the field of epidemiology in Health Region 9. The study included 396 participants, with data collected between March and July 2023. The study found that the majority of respondents were female (64.9%), with a median age of 35 years (ranging from 30 to 45). Approximately 68.9% of participants held the position of public health officer, and 86.6% had completed a bachelor’s degree. The proportion of individuals self-assessing their epidemiological competency at a high to the highest level included their ability to establish cooperation with communities in their area of responsibility for disease prevention and control. Additionally, the proportion of those indicating a high to the highest level of need for epidemiological development included competencies related to investigating diseases and formulating assumptions for disease investigations within their area of responsibility. The study also identified a significant statistical relationship between gender, epidemiological training, and competency scores (p<0.05). This suggests that gender and epidemiological training impact the competency levels of public health personnel in Health Region 9. In conclusion, the results of the competency assessment and the identification of development needs will serve as a framework for planning and enhancing the public health workforce in Health Region 9. The goal is to ensure their effectiveness in disease prevention and control at all levels.